The mediator's handbook : skills and strategies for practitioners - Charlton, Ruth; Dewdney, M.S.; Charlton, Geoff; Boulle, Laurence (Pyrmont, N.S.W. Thomson Reuters (Professional) Australia Limited, 2014)
Annotation. THE MEDIATOR'S HANDBOOK THIRD EDITION is an established and highly respected work which assists both experienced and newly qualified mediators who wish to expand their range of skills in this ever-evolving field. The mediation process is explained in simple steps applicable to all forms of dispute, whether it be commercial, workplace, family, neighbourhood and environmental. It clearly outlines the required skills, techniques and strategies, especially communication skills. Importantly, variations to the mediation process are explained as are the roles of advisers, support persons and interpreters. In this Third Edition, there has been significant revision to reflect new developments in mediation since the previous edition published in 2004.
Includes index.
Keywords: Mediation -- Handbooks, manuals, etc; Dispute resolution (Law) -- Australia -- Handbooks, manuals, etc; Mediation -- Australia -- Case studies